2015
DOI: 10.1039/c4cp05151c
|View full text |Cite
|
Sign up to set email alerts
|

Phosphine and phosphine oxide groups in metal–organic frameworks detected by P K-edge XAS

Abstract: Phosphine metal-organic frameworks (P-MOFs) are crystalline porous coordination polymers that contain phosphorus functional groups within their pores. We present the use of X-ray absorption spectroscopy (XAS) at the P K-edge to determine the phosphine to phosphine oxide ratio in two P-MOFs with MIL-101 topology. The phosphorus oxidation state is of particular interest as it strongly influences the coordination affinity of these materials for transition metals. This method can determine the oxidation state of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 33 publications
2
12
0
Order By: Relevance
“…Further evidence that no electronic interaction is responsible for the selectivity change was provided by preparing MOFs that feature strong coordinative bonds with Co such as phosphine MOFs (P-MOFs) 15,[36][37][38] . Such phosphine solid ligands can coordinate Co as supported by the literature 39 and by our DFT P-Co binding energies ( Supplementary Table 15 and Suplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Further evidence that no electronic interaction is responsible for the selectivity change was provided by preparing MOFs that feature strong coordinative bonds with Co such as phosphine MOFs (P-MOFs) 15,[36][37][38] . Such phosphine solid ligands can coordinate Co as supported by the literature 39 and by our DFT P-Co binding energies ( Supplementary Table 15 and Suplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…reported the coordination structure of FeBTC-MOF by EXAFS and XANES and confirmed that the unsaturated metal building units have Fe 3+ states. F. L. Morel et al 15 . reported the XANES spectra at P K-edge of phosphine and phosphine oxide functionalized framework materials to investigate their structural topology.…”
Section: Introductionmentioning
confidence: 99%
“…A qualitative proof for the incorporation of multiple linkers is usually unproblematic and can be confirmed by IR spectroscopy, XPS, XAS, solid‐state NMR spectroscopy and in some cases by single‐crystal analysis ( D ) . Moreover, UV/Vis spectroscopy can be used to prove the incorporation of certain linkers and might be able to quantify the linker ratios for certain systems …”
Section: Mixed‐linker Metal–organic Frameworkmentioning
confidence: 99%